2016
DOI: 10.3233/asy-161366
|View full text |Cite
|
Sign up to set email alerts
|

The multilayer shallow water system in the limit of small density contrast

Abstract: We study the inviscid multilayer Saint-Venant (or shallow-water) system in the limit of small density contrast. We show that, under reasonable hyperbolicity conditions on the flow and a smallness assumption on the initial surface deformation, the system is well-posed on a large time interval, despite the singular limit. By studying the asymptotic limit, we provide a rigorous justification of the widely used rigid-lid and Boussinesq approximations for multilayered shallow water flows. The asymptotic behaviour i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…These stability conditions are rigorously characterized in [40], where a general criterion of hyperbolicity and local well-posedness is given, under a particular asymptotic regime and weak stratification assumptions of the densities and the velocities. A similar study has been realized in [25] in the limit of small density contrast. It is shown that, under reasonable conditions on the flow, the system is well-posed on a large time interval.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…These stability conditions are rigorously characterized in [40], where a general criterion of hyperbolicity and local well-posedness is given, under a particular asymptotic regime and weak stratification assumptions of the densities and the velocities. A similar study has been realized in [25] in the limit of small density contrast. It is shown that, under reasonable conditions on the flow, the system is well-posed on a large time interval.…”
Section: Introductionsupporting
confidence: 75%
“…Even if the maximum admissible CFL is reduced, it is a remarkable result to find that taking one of the two stabilization constants to zero can be sufficient to obtain linear stability. These results may be set in relation with the optimized stability criteria issuing from the non-linear study, that is the one-dimensional relaxed condition (25) discussed in Remark 3.6. As the non linear study requires both α and γ to be strictly positive, only the case α = γ is explored in Fig.…”
Section: Linear Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation